Prevalence of Cardiovascular Risk Factors among Chronic Kidney Disease Patients Undergoing Hemodialysis in a Tertiary Care Center, Kathmandu, Nepal - Pokhrel, A; Gyawali, P.; Pokhrel, BR; Khanal, M P; Manandhar, D N; Bwititi, P; Nwose, EU (Nepal Medical College Journal, 2019)
The risk of cardiovascular disease is higher in chronic kidney disease patients compared to the general population and its impact is higher in developing countries compared to the developed countries. With this background in mind, we aimed to evaluate the prevalence of different cardiovascular risk factors in patients on maintenance hemodialysis in a tertiary care center. Chronic kidney disease patients aged 18 years and above who were under maintenance hemodialysis in the hemodialysis unit of Nepal Medical College were included in the study. Pre-dialysis venous blood samples from the participants were collected and analyzed for serum calcium, phosphorus, total protein, albumin and hemoglobin. Calcium phosphate product was calculated. Out of 100 study participants, 52% were male and 48% were female. Age-wise distribution showed 38% of the participants were below 40 years. The mean age of the participants was 45.86 ± 14.4 years. Ninety-three percent had hypertension and 29% had diabetes mellitus. Hypocalcemia was present in 80%, hyperphosphatemia was seen among 81% and high calcium phosphate product was present in 33% of the participants. Low hemoglobin (< 10gm/dL) was found in 86%. The cardiovascular risk trend in the Nepalese chronic kidney disease population is fairly different compared to the western population. Participants were younger. Prevalence of hypertension and diabetes was high. The high prevalence of anemia might be due to unaffordability of the participants for regular erythropoietin therapy. Inadequately managed hyperphosphatemia despite the widespread use of phosphorus binders, is still a major clinical challenge in patients on hemodialysis.